E-business in Micro Companies: Lessons learned - Sternad Zabukovšek Simona; Šišovska Irena; Mravljak, Monika; Bobek, Samo (Naše gospodarstvo/Our economy, 2015)
E-business is entering its mature stage. E-business in large companies has been researched in several surveys, whereas SMEs and micro companies have been researched less often. Micro companies are, together with SMEs, a critical part of national economies worldwide; both are central to the EU’s development strategies. It is well known that, in an information society, business models are driven by e-business concepts, and e-business models are emerging. An in-depth understanding of e-business use in micro companies is crucial for the success of such companies. The main purpose of this paper is to research the intensity of e-business use, advantages and disadvantages of e-business, the biggest problems of e-business implementation/maintenance, and attitude toward trends of e-business in micro companies. The paper presents findings from a survey carried out on a sample of micro companies. Data were collected via an e-questionnaire, and results were calculated using SPSS. The data confirmed that e-business in micro companies is most often used in connection with e-banking; e-business with the government also appears to be very important.